Effect Of HHO On Emissions And Efficiency In Two Stroke Engine 150cc - J. W. Paletekan; S. Suwandi; Tri Ayodha Ajiwiguna; Eddy Ariffin (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2018)
Emission generated by motor vehicles is one of the environmental pollution and it can interfere with the health, especially on the 2-stroke engine in which the emissions are greater than the 4-stroke engine. In this study, HHO, generated by electrolysis process in a reactor, was injected into 2-stroke engine. A test method called "idle" was performed using SNI 19-7118.3-2005 standard so that the emissions generated on the 2-stroke engine was reduced. HHO was added by forwarding the gas through the hose on bubbler and entering the air hose filter in the carburator. The reactors were conditioned to produce 400 ml electrolysis and a catalyst such as KOH with different concentrations. It affected the rate of HHO flow. Prior to the addition of HHO, levels of HC was 6453 ppm at 6000 rpm and it decreased by 31.66% when the HHO was added. This decrease also occurred in CO, where the levels of CO fell from 2. 56% to 1.75 %. On the other hand CO2 levels increased from 2.23 % to 4.22 % with the HHO addition. In this study, it was found that the best HHO rate was147 mLpm. Besides, at 6000 rpm, the engine efficiency increases 5.1 % when 147 mLpm HHO was added.